Prospecções à autenticidade: o uso do mito grego como possibilidade de se pensar o (docente)feminino - Rodrigues, Claudia Flores (2008)
In this work intends to grow a reflection it remains in that measured the use of the myth as metaphor to think on her the feminine, it can limit or powerful the educational work. The thematic accuses X woman in the universal history he/she has as conductive thread the myth of Pandora, in what refers to the blame attributed to the woman and the blames that the women carry as reflex of a Jewish-Christian education in times of modernity or the triple day of work reflex of the life of this century. As theoretical reflectors " of analysis, he/she appears the gender, tends socially in view the attempt of understanding of the relationship built between men and women, as well as of the construction of the woman teacher's feminine subjectivity. Divided in four moments, the work begins with a narrative fictitious maid starting from real facts. Further on, teacher Ethos's character that will dialogue with the protagonist of the history about the human's propositions appears, what is worth the own narrator's internal dialogues and explicit the authors that go being introduced in your ideas along the narrative. The third part is the interviews (real) with teachers that talk about some of your existences. Finally, after the analysis of the interviews, the absolution of Pandora and the presentation of the categories observed in the interviews it works as backdrop for a reflection on the subject's formation and the use of the Greek myth as possibility of to think on him and to bring to the surface searches on the human, in the case of this work, the woman.